Prospects and pitfalls in combining eye tracking data and verbal reports - Laura Helle (EARLI, 2017)
It is intuitively appealing to try to combine eye-tracking data and verbal reports when investigating medical image interpretation. However, before collecting such data, important decisions have to be made including exactly when and how to collect the verbal reports. The purpose of this methodological article is to reflect upon the pros and cons of different solutions and to offer some guidelines to investigators. We start by exploring the ontology of vision and speech production and the epistemology of eye movements to grasp what fixations and verbal reports actually reflect. We are also interested in the major constraints of the two systems. Second, we elaborate on two dominant investigational approaches to verbal accounts, namely concurrent think-aloud and Chi's explanations, and move on to other approaches. Third, we present and critically evaluate studies from the literature on medical image interpretation that have sought to contrast or integrate eye movement data and verbal reports. Fourth, we conclude with some practical guidelines and suggestions for further research.